Role of Innovation on Green Economic Growth: Empirical Analysis from the Countries of the Western Balkans - Plakaj Vërbovci, Marigonë; Gara, Atdhetar; Abazi Alili, Hyrije (Ekonomika, 2024)
The impact of innovations on the growth of the green economy is a crucial aspect for a country’s economy. The promotion of these innovations and investments is also vital for sustainable and long-term development. This paper aims to present the role of innovation on green economic growth in the countries of the Western Balkans (Kosovo, Albania, North Macedonia, Montenegro, Bosnia and Herzegovina and Serbia) over a 13-year period, from 2010 to 2022.Data for the research were obtained from the World Bank and the Global Economy Database, where the study data type is Panel. The econometric models used are: the ordinary least squares (OLS) model, the Fixed Effect (FE) model, the Random Effect (RE) model and the Hausman Taylor (HTH) model. The dependent variable is green economic growth, while the independent variables include the innovation index (INV), research and development expenditures (R&D), information technology exports (ITE), patent applications from residents (PA), manufacturing output (MAN), business freedom index (BFI), investment freedom index (IFI), and economic freedom index (EFI). The findings of this paper show that the countries of the Western Balkans should promote key factors such as: innovation as an important driver, with a positive impact on green economic growth; research and development expenses; patent applications, and favorable business and economic environments to facilitate long-term green economic growth and promote environmental sustainability. The results indicate that the coefficient for innovation is positive (B=0.41) and statistically significant at the 1% level, supporting the hypothesis that the increase in innovation has a positive impact on green economic growth in the countries of the Western Balkans.
Keywords: Green economic growth; Innovation; Research and Development; Western Balkans